Relationship between dietary patterns and overactive bladder: a cross sectional study of NHANES 2013 to 2023 - Ding, Yiming; Mou, Yaru; Wang, Dongming; Niu, Zeyong; Xin, Pengge; Zhou, Yu; Song, Guoxin; Xu, Hongjia; Wang, Jian (Frontiers in Nutrition, 2025)
BackgroundDietary patterns, as a comprehensive dietary indicator, may influence the risk of developing overactive bladder (OAB). However, it remains unclear whether dietary patterns independently affect the development of OAB.ObjectiveThis study aimed to identify specific dietary patterns using principal component analysis (PCA) and evaluate their associations with the risk of OAB, thereby providing new insights for OAB prevention and management.MethodsDietary patterns were identified by applying PCA, and their associations with OAB risk were analyzed. After adjusting for three known confounders (age, sex, and BMI), four key dietary patterns were determined: (1) PC5: Antioxidant-balanced pattern, OR = 0.96, 95% CI (0.94–0.97), p < 0.05; (2) PC16: Diversified low-alcohol pattern, OR = 0.92, 95% CI (0.89–0.94), p < 0.05; (3) PC18: Whole-grain high-alcohol pattern, OR = 1.04, 95% CI (1.01–1.07), p < 0.05; (4) PC22: High-fiber low-sugar pattern, OR = 0.93, 95% CI (0.90–0.96), p < 0.05.ResultsThe findings indicated that the antioxidant-balanced (PC5), diversified low-alcohol (PC16), and high-fiber low-sugar (PC22) dietary patterns were associated with a decreased risk of OAB, while the whole-grain high-alcohol pattern (PC18) exhibited a dual effect. Specifically, when considered independently, the high-fiber low-sugar pattern showed a protective effect; however, when combined with the whole-grain high-alcohol pattern, it increased the risk of OAB.ConclusionDietary patterns are independent factors influencing the development of OAB. In particular, the antioxidant-balanced, diversified low-alcohol, and high-fiber low-sugar patterns help reduce OAB risk, whereas the whole-grain high-alcohol pattern exerts a dual effect.